Impact of venetoclax monotherapy on the quality of life of patients with relapsed or refractory chronic lymphocytic leukemia: results from the phase 3b VENICE II trial. Issue 2 (28th January 2022) - Cochrane, Tara; Enrico, Alicia; Gomez-Almaguer, David; Hadjiev, Evgueniy; Lech-Maranda, Ewa; Masszi, Tamas; Nikitin, Eugene; Robak, Tadeusz; Weinkove, Robert; Wu, Shang-Ju; Sail, Kavita R.; Pesko, John; et al.
Abstract: Venetoclax, a potent B-cell lymphoma-2 (BCL-2) inhibitor, has demonstrated clinical efficacy in chronic lymphocytic leukemia (CLL). VENICE II is an open-label, single-arm, phase 3b study (NCT02980731) evaluating the impact of venetoclax monotherapy (400 mg once daily) for ≤2 years on health-related quality of life (HRQoL) of patients with relapsed/refractory CLL. The primary endpoint was mean change in the global health status (GHS)/quality of life (QoL) subscale of the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ-C30) from baseline to Week 48. Overall, 210 patients received ≥1 dose of venetoclax; median treatment duration was 67.4 weeks. The primary endpoint was met with mean improvement of +9.3 points ( n  = 156, 95% confidence interval 6.1–12.5; p =.004) in GHS/QoL. At Week 48, clinically meaningful improvements were observed for role functioning, fatigue, and insomnia domains of EORTC QLQ-C30, suggesting venetoclax monotherapy has a positive impact on HRQoL. No new safety signals were reported.